TAXONOMIC IDENTIFICATION AND PHYLOGENETIC CHARACTERIZATION OF TRICHODERMA SPECIES ISOLATED FROM THE SOILS OF THE BUKHARA REGION (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Studying Trichoderma species represents a large practical and theoretical interest in connection with their use in human activities. The widespread use of these mushrooms requires the study of their environmental features, species diversi-ty.Trichoderma  fungi are widespread in nature. The systematic position of fungi of the genus Trichoderma studied from soil samples of the Bukhara region. Isolated fungus according to the identifier Rifai are classified as Trichoderma koningi, Trichoderma harzianum, Trichoderma aureoviride, Trichoderma longibrachiatum.